The Influence of Cost Management Strategies on Financial Performance among Selected Manufacturing Businesses in Tagum City - Guibao, Kimberly Tiara S.; Hilamon, Kaye Angela V.; Sepe, Ma. Divine L.; Flores, Joe Mari N. (Future Science / FSH-PH Publications, 2025)
In today’s competitive global economy, manufacturing companies face constant challenge in managing costs effectively while maintaining financial performance, and meeting customer demands. While the significance of cost management is widely acknowledged, its impact on the financial performance of manufacturing businesses in Tagum City remains underexplored. This study examined the influence of cost management strategies on financial performance among selected manufacturing businesses in Tagum City. Specifically, it sought to determine whether material, labor, and overhead costing, as the domains of cost management strategies impacted their financial performance. In addition, a quantitative, non-experimental, descriptive-correlational design was employed. The data collected from 179 managers/owners who were selected through simple random sampling and surveyed using structured questionnaires. Furthermore, statistical tools applied included the Mean, Pearson’s r, and Multiple Regression Analysis. The results revealed that effective cost management strategies have a significant impact on financial performance. In particular, financial performance was significantly influenced by material and labor costs, while overhead costs demonstrated less impact. Therefore, this study underscores the significance of effective cost management strategies in improving financial sustainability and driving business growth, thereby contributing to SDG 8 (Decent Work and Economic Growth).